Ambiguity in the evaluation of the effective action on the cone - Iellici, Devis; Moreira Jr., Edisom S. [UNESP] (American Physical Society (APS), 1999)
An ambiguity in the computation of the one-loop effective action for fields living on a cone is illustrated. It is shown that the ambiguity arises due to the noncommutativity of the regularization of ultraviolet and (conical) boundary divergencies. ©1999 The American Physical Society.